Evaluation of the effectiveness of a 7-week minimal guided and unguided cognitive behavioral therapy-based stress-management APP for students - Elisabeth Margarete Weiss; Mona Harder; Siegmund Staggl; Bernhard Holzner; Verena Dresen; Markus Canazei (BMC Public Health)
Abstract Stress during academic training is a significant issue for students, which intensified during the COVID-19 pandemic. Internet-based stress management programs are an attractive, low-threshold and cost-effective option for students at universities. The present randomized controlled intervention study examined the efficacy of a newly developed seven-week minimal guided (with optional e-Coach support) and unguided stress management training (iSMT) App based on cognitive behavioral therapy techniques (CBT) for university students. Participants (guided iSMT version: n = 118; unguided iSMT version: n = 123) were compared to a previous study’s passive psychoeducation group (n = 123) and waiting control group (n = 130). Participants were tested at pre- and post-intervention with the Depression Anxiety Stress Scale-21 (DASS-21), the Response Styles Questionnaire (RSQ) and the Emotion Regulation Questionnaire (ERQ). Both iSMT interventions significantly reduced perceived stress compared to the psychoeducation group and the waiting-list control group (all ps < .001; all ηp2 > .056), but no significant differences were found between the two versions of the iSMT. All intervention groups further showed improved emotion regulation (higher reappraisal) and coping (lower symptom-related rumination) strategies, with a small effect. These findings support iSMT as a cost-effective, accessible intervention for student stress management, offering benefits beyond traditional psychoeducation.